Implementation Talent of Management for Organization Sustainable: Literature Review: Human Resource - Saepudin, Tubagus Hedi; Kamsariaty, Kamsariaty; Soekirman, Atong; Suhendra, Agus; Suhartini, Suhartini (Green Publisher, 2025)
The purpose of this literature study is to develop a hypothesis regarding the influence between variables that can be used for further research in the field of human resource management. The article, a literature review of the implementation of talent management on company sustainability, is a scientific literature article in the field of human resource management. The approach used in this literature review is qualitative and descriptive. The data collection technique is to use a literature study or review relevant previous articles. The data used in this descriptive qualitative approach comes from previous research relevant to this research and is sourced from academic online media such as Thomson Reuters, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Web of Science, Sinta Journal, DOAJ, EBSCO, Google Scholar and digital reference books. In previous research, each relevant previous article was used to review each independent variable. The results of this literature review article are: 1) Talent Management affects Company Sustainability; 2) Ability affects Company Sustainability; 3) Assessment affects Company Sustainability; and 4) Mentoring affects Company Sustainability.